Volumetric and Viscometric Behaviour of Acrylic Esters with Hexane-2-ol at T= (298.15 And 308.15) K - Patil Sujata S.; Mirgane Sunil R. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Densities and viscosities for the three binary liquid mixtures of methyl acrylate, ethyl acrylate and butyl acrylate with hexane-2-ol at temperatures 298.15 and 308.15 K and at atmospheric pressure were measured over the whole composition range. These values were used to calculate excess molar volumes and deviation in viscosities which were fitted to Redlich-Kister polynomial equation. Recently proposed Jouyban Acree model was also used to correlate the experimental values of density and viscosity. The mixture viscosities were correlated by Grunberg-Nissan, Tamura and Kurata, McAllister’s three and four body model equations. The calculated excess molar volume and deviation in viscosity were found to be positive and negative respectively for all the binary liquid mixtures at 298.15 and 308.15 K temperatures.